Ultrafast Electron and Hole Relaxation Pathways in Few-Layer MoS2 - Nie, Zhaogang (2015)
Femtosecond optical pump–probe spectroscopy is employed to elucidate the band-selective ultrafast carrier dynamics of few-layer MoS2. Following narrowband resonant photoexcitation of the exciton A transition, the subpicosecond to picosecond relaxation dynamics of the electron and the hole at the K valley are separately interrogated by a broadband probe pulse. The temporal evolution of the spectral first moment reveals nonexponential intravalley relaxation dynamics in the conduction band. Fluence dependence measurements suggest that this relaxation process is predominantly mediated by acoustic phonon emission. Intervalley scattering of carriers from the K valley to the extrema of the conduction and valence bands is also observed via the decay of the spectral zeroth moment. In addition, second-order Raman scattering leads to the emergence of sidebands in the normalized differential transmission spectra. The observed two-phonon energies and the fluence-dependent time constants suggest that the E1g longitudinal optical (LO) phonon and the LA phonon participate in intervalley scattering in the conduction and valence bands, respectively. Ab initio nonadiabatic molecular dynamics simulations yield time constants of 0.80 and 0.72 ps for intra- and intervalley electronic relaxation, respectively; the latter agrees well with experiment. Finally, the normalized differential transmission spectra reveal a two-electron shake-up satellite that originates from band-edge radiative recombination and the simultaneous excitation of a hole from Kv1 to Kv2. From its spectral position, a Kv1–Kv2 spin–orbit splitting of 1166 ± 1 cm–1 is deduced. The observation of the two-electron transition points to the existence of strong electron correlation in photoexcited few-layer MoS2.